2016
DOI: 10.1007/s11332-016-0279-8
|View full text |Cite
|
Sign up to set email alerts
|

The acute effect of exercise intensity on free throws in young basketball players

Abstract: Purpose Free throws (FT) accuracy is a major determinant of performance in basketball game. However, the effect of exercise intensities on FT accuracy has not been well studied. The aim of the present study was to examine the effect of different exercise intensities on FT accuracy in young male basketball players. Methods For this aim, 22 basketball players (age 16.12 ± 1.16 years, body mass 76.4 ± 13.3 kg and height 186.4 ± 8.9 cm), classified into 2 age groups (younger 15.28 ± 0.48 years, n = 11; older 16.97… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…To the best of our knowledge, the present study is the first to specifically examine the variation in JS% induced by exercise intensity. These results are in line with those of previous research on the effect of exercise intensity on FT ( Padulo et al, 2015a ; Mokou et al, 2016 ) and three-point shot (3S) accuracy ( Ardigò et al, 2018 ), which showed a significant reduction in shot accuracy at 80HR compared to 0HR and 50HR. Thus, exercise intensity exerted a similar effect on the 3S, JS, and FT, yet, a difference can be identified between the 3S and JS compared with the FT. Namely, FT is not a game-play flow-driven basketball fundamental, given that it is basically shot without any defence pressure and during a game-play pause.…”
Section: Discussionsupporting
confidence: 92%
“…To the best of our knowledge, the present study is the first to specifically examine the variation in JS% induced by exercise intensity. These results are in line with those of previous research on the effect of exercise intensity on FT ( Padulo et al, 2015a ; Mokou et al, 2016 ) and three-point shot (3S) accuracy ( Ardigò et al, 2018 ), which showed a significant reduction in shot accuracy at 80HR compared to 0HR and 50HR. Thus, exercise intensity exerted a similar effect on the 3S, JS, and FT, yet, a difference can be identified between the 3S and JS compared with the FT. Namely, FT is not a game-play flow-driven basketball fundamental, given that it is basically shot without any defence pressure and during a game-play pause.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding free throw efficacy, our results are in accordance with previous literature reports, a rate of *60% success in shoots performed after exercises at high intensity, such as above 80% of maximal heart rate (Mokou et al, 2016;Padulo et al, 2015a). Our hypothesis was that b-alanine supplementation could enhance the workout capacity, delaying the fatigue process induced by RSA and providing conditions to perform the free throws under a better physiological condition, as observed by Hoffman et al (2014) for elite soldiers during shooting tasks with an assault rifle.…”
Section: Discussionsupporting
confidence: 92%
“…A few studies reported a correlation among lower-limb based explosive movements such as jump, sprint, and agility in basketball [ 4 , 10 ]. So, if a significant association is found between these movements and single-leg CMJ performance, the results may help practitioners and athletic trainers to focus on unilateral performance parameters to optimize sprint and agility, which are critically important for basketball performance [ 28 , 29 , 30 ]. Furthermore, the impact of the age factor on the aforementioned relationship remains unclear.…”
Section: Introductionmentioning
confidence: 99%